Long-term treatment outcomes from a patient's perspective with Treacher Collins syndrome. Issue 5 (27th May 2021) - Smith, Francis; Fowler, Peter; Ellis, Pamela
Abstract : The management of patients with Treacher Collins Syndrome (TCS) is complex and involves many different specialists within multidisciplinary teams (MDT). The treatment pathway extends from birth well into adulthood and is associated with a heavy burden of care. Due to the extensive nature of the interaction with these patients, MDT members have opportunities to provide enhanced patient-centred care and support.This case report provides an overview of the current knowledge of the aetiology of TCS, the management of these patients and provides a unique perspective from one of the coauthors who has TCS and reports on his treatment experiences and long-term treatment outcomes. By having a better understanding of the impact of TCS and treatment provided, MDT members can not only provide improved clinical treatment but also offer improved patient experiences for those with craniofacial anomalies in particular an increased awareness of the psychosocial challenges they endure.